ric 2022
DOI: 10.7764/ric.00017.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Ore Tailing and Glass Powder on Concrete Properties

Abstract: The aim of this research is to test the characteristics of concrete by substitute fine aggregate with iron ore tailings and partial glass powder as in the place of cement. Concrete with waste products such as glass powder and iron ore tailings offers technical, economic and environmental advantages. In this experimental investigation, glass powder is replaced with cement by 10%, 20% and 30% and iron ore tailings with fine aggregates by 30% which is the optimum percentage. To study the role of glass powder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The research suggested using 10% GP and 30% iron ore tailing, which enhances the concrete strength. On the other hand, water absorption and workability decreased with the increase in GP 25 . Rao et al 26 investigated the influence of replacing 20% of sand with ground granular blast furnace slag and cement with 6% nano-silica and 10% rice husk ash on the strength and durability of concrete.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The research suggested using 10% GP and 30% iron ore tailing, which enhances the concrete strength. On the other hand, water absorption and workability decreased with the increase in GP 25 . Rao et al 26 investigated the influence of replacing 20% of sand with ground granular blast furnace slag and cement with 6% nano-silica and 10% rice husk ash on the strength and durability of concrete.…”
Section: Introductionmentioning
confidence: 94%
“…The results showed that the concrete strength increased with the replacement ratio up to 12%. Dhanabal et al 25 investigated the influence of replacing 30% of sand with iron ore tailing constant for all mixes and 0%, 10%, 20%, and 30% of cement with glass powder (GP) on the strength and durability of concrete. The research suggested using 10% GP and 30% iron ore tailing, which enhances the concrete strength.…”
Section: Introductionmentioning
confidence: 99%